1995
DOI: 10.1016/0269-7491(95)00022-j
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between copper and cadmium modify metal organ distribution in mature tilapia, Oreochromis mossambicus

Abstract: Sexually mature female tilapia were exposed to sublethal concentrations of waterborne Cu and/or Cd over 6 days, and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(42 citation statements)
references
References 49 publications
3
38
0
Order By: Relevance
“…These authors proposed two hypotheses for their results: (a) there may be secondary Cu uptake from Cu excreted from the bile into the intestine, or (b) the intestine may serve as a possible excretion route for the metal (Mazon and Femandes, 1999). Pelgrom et al (1995) also observed similar results in tilapia exposed for 6 and 11 days to 20 and 100 µg/L Cu. Moreover, higher Cu concentrations in the intestines may be related to the fact that marine teleosts exhibit higher drinking rates than freshwater teleosts (Jobling, 1995).…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…These authors proposed two hypotheses for their results: (a) there may be secondary Cu uptake from Cu excreted from the bile into the intestine, or (b) the intestine may serve as a possible excretion route for the metal (Mazon and Femandes, 1999). Pelgrom et al (1995) also observed similar results in tilapia exposed for 6 and 11 days to 20 and 100 µg/L Cu. Moreover, higher Cu concentrations in the intestines may be related to the fact that marine teleosts exhibit higher drinking rates than freshwater teleosts (Jobling, 1995).…”
Section: Discussionsupporting
confidence: 81%
“…These results support the hypothesis that the liver is the major storage and regulatory tissue involved in Cu homeostasis. Similar results have been observed in sea bream (Wong et al, 1999), rainbow trout (Handy, 1993;Miller et al, 1993), tilapia (Pelgrom et al, 1995;Ay et al, 1999), and the Senegales sole (Arellano et al, 1999). Therefore, after Cu exposure, the liver of olive flounder is clearly a more important storage tissue than other tissues.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations